Penguatan Kualitas Pelayanan Gerejawi melalui Edukasi Keluarga dan Etika Pelayanan bagi Hamba Tuhan di GBT Wilayah Samarinda - Tri Astuti; Chandra Kirana Luhur (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PkM) aims to strengthen the quality of church ministry through family education and ministry ethics education for church ministers in the Gereja Beth-El Tabernakel (GBT) Samarinda Region. The PkM was conducted in the form of a two-session seminar covering family education and ministry ethics education, employing lecture, discussion, and question-and-answer methods. Participants included pastors, ministers, church workers, and elders from GBT churches in the Samarinda area. The results indicate that family education encouraged participants to re-examine the role of family as the foundation of ministry, while ministry ethics education reinforced the understanding of ministry as an honor, a form of sacrifice, and a continuous process of personal transformation. The integration of these two components enhanced participants’ awareness of the importance of life balance, moral integrity, and exemplary conduct in ministry. This program contributes to the development of healthier, more balanced, and character-centered church ministry.